IMPLEMENTASI FACE DETECTION PADA SMART CONFERENCE MENGGUNAKAN VIOLA JONES - Freddy Nur Afandi; Ramses Parulian Sinaga; Yuthsi Aprilinda; Fenty Ariani (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2019)
In the study of computer vison, facial recognition early stages of the process required to determine the face itself. The process is the process of human detection (face detection). But generally the facial image has the size and shape of the face is varied, and the lighting is erratic or changed to change so as to make the face detection becomes more difficult to detect. In this thesis, the author uses the Viola-Jones method for detecting human faces (face detection). The result of this thesis is the implementation of the system of the human face detection on the Smart Conference with Viola-Jones method.